Estudo do Índice Biometeorológico Humidex e de sua Correlação com Óbitos em Campinas - Abreu, João Luís C. De; Costa, Paula D. P.; Avila, Ana Maria H. de; Faria, Eliana C. de (Proceedings of the Regional School of Applied Computing for Health (ERCAS), 2021)
The present work conducted a regional analysis on the impact of extreme events identified by the biometeorological index Humidex on the deaths from cardiovascular diseases in Campinas. We conducted a comparative analysis of daily death distributions under extreme event versus control-days (MannWhitney U test). Although the literature indicates a correlation between Humidex values and the increase in deaths, we did not found a significant statistical difference.